2023
DOI: 10.1111/rda.14432
|View full text |Cite
|
Sign up to set email alerts
|

The role of GnRH in Tibetan male sheep and goat reproduction

Wangsheng Zhao,
Michael Adjei,
Zhenzhen Zhang
et al.

Abstract: The hypothalamic‐pituitary‐gonadal (HPG) axis connects the hypothalamus, pituitary gland, and gonads. The regulation of reproductive processes includes integrating various factors from structural functions and environmental conditions in the HPG axis, with the outcome indication of these processes being the pulsatile secretion of gonadotropin‐releasing hormone (GnRH) from the hypothalamus. These factors include feed consumption and nutritional condition, sex steroids, season/photoperiod, pheromones, age, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Remarkably, we noticed that these proteins were downregulated in the mTOR signaling in the ELC vs. PLC group, suggesting their involvement in goose male fertility and spermatozoa production at the critical stage of the laying cycle. Our findings also demonstrated that several other interesting pathways were enriched in testicles tissues of the Jilin white goose, including the MAPK [ 37 ], Notch [ 38 ], GnRH signaling pathways [ 39 ], and other pathways related to reproductive hormone secretion and metabolic, which suggests that goose male reproduction is regulated with multiple signaling pathways and proteins that were widely studied to be associated with reproduction. It is worth noting that the metabolic pathways in the KEGG enrichment were significantly enriched, which suggested that may are cellular differences in testicular tissue in Jilin white geese with high and low sperm motility, and many of the DEPs identified may play a function in controlling cell metabolism, thereby involving in the regulation of sperm motility in Jilin white geese.…”
Section: Discussionmentioning
confidence: 65%
“…Remarkably, we noticed that these proteins were downregulated in the mTOR signaling in the ELC vs. PLC group, suggesting their involvement in goose male fertility and spermatozoa production at the critical stage of the laying cycle. Our findings also demonstrated that several other interesting pathways were enriched in testicles tissues of the Jilin white goose, including the MAPK [ 37 ], Notch [ 38 ], GnRH signaling pathways [ 39 ], and other pathways related to reproductive hormone secretion and metabolic, which suggests that goose male reproduction is regulated with multiple signaling pathways and proteins that were widely studied to be associated with reproduction. It is worth noting that the metabolic pathways in the KEGG enrichment were significantly enriched, which suggested that may are cellular differences in testicular tissue in Jilin white geese with high and low sperm motility, and many of the DEPs identified may play a function in controlling cell metabolism, thereby involving in the regulation of sperm motility in Jilin white geese.…”
Section: Discussionmentioning
confidence: 65%
“…In livestock, GnRH also plays a wide range of regulatory roles ( 36 ), but some factors are unknown. Five studies analyzed the use of a GnRH agonist versus a control.…”
Section: Discussionmentioning
confidence: 99%
“…Beckett and Lean reported that GnRH administration before 40 days after delivery may shorten the time to first estrus but was not associated with the final reproductive performance of the cow ( 39 ). A review described the current research on GnRH function in sheep reproduction and indicated that GnRH plays a role in many aspects of reproduction ( 36 ). However, there are no direct reports on whether GnRH can regulate embryo implantation or its mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…T and E 2 are indispensable steroid hormones for maintaining normal male reproductive function, and their levels are closely related to spermatogenesis. Consequently, GnRH, FSH, LH, T, and E 2 collectively construct a complex regulatory network within the endocrine system, intimately intertwined with testicular reproductive function, collaboratively upholding male reproductive health [ 67 ]. Nevertheless, in cases of HPGA dysfunction, disruptions in reproductive hormones may emerge, triggering testicular insufficiency and hindering sperm production, development, and maturation, ultimately culminating in MI.…”
Section: Discussionmentioning
confidence: 99%